2006
DOI: 10.1002/casp.869
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between past contraceptive behaviour, self‐efficacy, and anticipated shame and guilt in sexual contexts among Norwegian adolescents

Abstract: What are the relationships between self-efficacy when communicating to the partner about use of contraception, stopping undesired intercourse, and perceived self-conscious emotions in sexual contexts? How does past contraceptive behaviour influence perceived self-efficacy? These research questions were studied among 399 10th grade students with coital experience in the county Nordland in Norway. Two dimensions of perceived emotional responses were identified in a hypothetical situation related to communicating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
3
1
Order By: Relevance
“…Over half of students in the study reported having masturbated, and over one-fourth reported having had premarital sexual intercourse. While these figures are lower than those obtained in the studies carried out in the West (Finer, 2007;Darroch, Singh, & Frost, 2005;Traeen & Kvalem, 2007), they are higher than those obtained in the studies carried out in the other societies of Islamic culture (Simbar, Tehrani, & Hashemi, 2005;Kadri et al, 2006). The results of this study compared with the results of other studies conducted in Turkey, observed lower rates of premarital sexual contact than those reported in the studies conducted in Western Turkey (Aras et al, 2007;Askun & Ataca, 2007) and similar to the rates reported in the studies conducted in Eastern Turkey (Donmez, 1999).…”
Section: Downloaded By [Uq Library] At 01:12 01 November 2014contrasting
confidence: 82%
See 1 more Smart Citation
“…Over half of students in the study reported having masturbated, and over one-fourth reported having had premarital sexual intercourse. While these figures are lower than those obtained in the studies carried out in the West (Finer, 2007;Darroch, Singh, & Frost, 2005;Traeen & Kvalem, 2007), they are higher than those obtained in the studies carried out in the other societies of Islamic culture (Simbar, Tehrani, & Hashemi, 2005;Kadri et al, 2006). The results of this study compared with the results of other studies conducted in Turkey, observed lower rates of premarital sexual contact than those reported in the studies conducted in Western Turkey (Aras et al, 2007;Askun & Ataca, 2007) and similar to the rates reported in the studies conducted in Eastern Turkey (Donmez, 1999).…”
Section: Downloaded By [Uq Library] At 01:12 01 November 2014contrasting
confidence: 82%
“…Because sexual values and the meaning of sexuality depend on the culture, the frequency of premarital sexual intercourse may vary from culture to culture. For example, while premarital sex is widespread in most western cultures with scarcely any significant differences between genders (Finer, 2007;Darroch, Singh, & Frost, 2005;Traeen & Kvalem, 2007), it is quite limited within Turkey and Islamic cultures of the east, especially for women (Kadri et al, 2006;Parla, 2001;Sakalli & Glick, 2003;Askun & Ataca, 2007). This difference could be associated with factors, such as the traditional value of virginity (Parla, 2001;Sakalli & Glick, 2003;Leiblum, Wiegel, & Brickle, 2003;Hirst, 2004) and sexual double standards (Marks & Fraley, 2005;Jonason & Fisher, 2009).…”
Section: Introductionmentioning
confidence: 91%
“…Third, the anticipated affective consequences of engagement in physical activity that were measured in the current study represent only a subset of possible emotions that could influence the adoption and maintenance of health behavior. Other emotions such as anticipated shame, regret, and guilt may also play a role (e.g., Abraham & Sheeran, 2004; Træen & Kvalem, 2006). Moreover, only positive emotions were considered for behavioral success and only negative emotions for behavioral failure, but in reality a mix of both positive and negative anticipated emotions are possible whether considering successful or unsuccessful engagement in physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Guilt is defined as an emotion that is aroused when an individual feels bad about a behavior (i.e., perceives that they have committed a transgression against someone) while still being okay with the self (Tangney, Wagner, Hill-Barlow, Marschall, & Gramzow, 1996). Specifically, research has shown that guilt can be very powerful as an influencing mechanism on health behaviors (Miller, Burgoon, & Hall, 2007;Tangney et al, 1996;Traeen & Kyalem, 2007). According to Lazarus (1991), guilt is aroused when an individual is made aware of how their behavior is responsible for causing harm (i.e., transgression) to others.…”
Section: Guilt and Antismoking Psasmentioning
confidence: 99%